Synthesis and antifungal activity of some new 6-substitutedarylimino-2-(4- chlorophenyl)-3-oxo-1,2,4,5-thiatriazines - Manna P.; Singh R.; Narang K.K. (My University, 2025)
6-Substitutedarylimino-2-(4-chlorophenyl)-3-oxo-1,2,4,5-thiatriazines (IV) have been synthesized by oxidative debenzylation and cyclization with molecular bromine in moistened chloroform from the corresponding 1-substitutedaryl-6-(4- chlorophenyl)-2-S-benzyliso-2-thiohydrazodicarbonamides (III). These 1,2,4,5-thiatriazines (IV) have also been prepared by the oxidation of corresponding 1-substituted aryl-6-(4-chlorophenyl)-2-thiohydrazodicarbonamides (V) with molecular bromine in ethanol, 1-Substitutedaryl-6-(4-chlorophenyl)-2- thiohydrazodicarbonamide (V) have been synthesized by reductive debenzylation with hydrogen sulphide in a solution of pyridine and triethylamine from the corresponding 1-substitutedaryl-6-(4-chlorophenyl)-2-S-benzyliso-2- thiohydrazodicarbonamides (III). S-benzylisothiohydrazodicarbonamides (III), in turn, were prepared by the condensation of 1-substitutedaryl-2-S- benzylisothiosemicarbazides (II) with 4-chlorophenylisocyanate. Thiatriazines (IV) have been characterized by their synthesis through alternative routes, element analyses, IR, 1H NMR, 13C-NMR and mass spectral data. Antifungal screening of the title compounds against ten fungi have been done by glass slides methods and their comparative findings have been critically examined. The compound containing p-chloroaryl group (IVc) was found to show maximum inhibitory effect (98.9%) against Collectotrichum sp. at a 500 μg/ml concentration.